Development of a synthetic affinity membrane for the purification of recombinant maltose binding proteins - Asongwe, Lionel Ateh Tantoh (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Biochemistry))--Stellenbosch University, 2008.